2004
DOI: 10.4143/crt.2004.36.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of the Cellular Processes in Uterine Leiomyomas: Omic Approaches and IGF-2 Association with Leiomyosarcomas

Abstract: Potentially significant pathogenetic cellular processes showed that down-regulated functional profiling has an important impact on the discovery of the pathogenic pathways in leiomyomas and leiomyosarcomas. GO analysis can also overcome the complexity of the expression profiles of cDNA microarrays and 2D protein analyses, via a cellular process level approach. Thereby, a valuable prognostic candidate gene, with real relevance to disease-specific pathogenesis, can be found at cellular process levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…It has been shown that PRDX2 may have a proliferative effect and plays a role in the matrix production (29). In a previous study, PRDX6, but not PRDX2, was found to be upregulated in the leiomyoma (30). A previous study suggested that hypoxia induces cell damage, act through antioxidant enzymes on quiescent cells inducing proliferation (31).…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that PRDX2 may have a proliferative effect and plays a role in the matrix production (29). In a previous study, PRDX6, but not PRDX2, was found to be upregulated in the leiomyoma (30). A previous study suggested that hypoxia induces cell damage, act through antioxidant enzymes on quiescent cells inducing proliferation (31).…”
Section: Discussionmentioning
confidence: 96%
“…CLIC4 is shown to exhibit varied expression and activity in several tumor types including ovarian, colon, bladder cancers, glioma, melanoma and even present in the exosomes ejected from human ovarian cancer cell lines. CLIC4 expression is positively correlated with tumor grade, lymph node metastasis, tumor invasion and poor overall survival in ductal adenocarcinoma of the pancreas (Bae et al, 2004;Dyrskjot et al, 2004;Alonso et al, 2007;Liang et al, 2013;Zou et al, 2016). Curiously, knockdown of CLIC4 in mouse liver cancer cells promotes apoptosis (Yu Q.Y.…”
Section: Clic4mentioning
confidence: 99%
“…It was reported that NAV2 was overexpressed in leiomyosarcoma and it was one of the signature genes used to distinguish between endometrial stromal sarcoma and leiomyosarcoma . KIF5C was upregulated and correlated with the leiomyosarcomas . Various studies have revealed that DCX was altered in uterine leiomyoma .…”
Section: Resultsmentioning
confidence: 99%
“…26 KIF5C was upregulated and correlated with the leiomyosarcomas. 27 Various studies have revealed that DCX was altered in uterine leiomyoma. 28 Altered DNA methylation at imprinted domains of MEST may mediate the association between HPV and the risk of invasive cervical cancer.…”
Section: Identification Of Differentially Expressed Genesmentioning
confidence: 99%